Rapid Assessment of the COVID-19 Impacts on the Galician (NW Spain) Seafood Sector - Villasante, Sebastian; Tubío, Ana; Ainsworth, Gillian; Pita, Pablo; Antelo, Manel; Da-Rocha, José María (Frontiers in Marine Science, 2021)
This paper aims to develop a rapid assessment of the COVID-19 impact on the Galician (NW Spain) seafood sector, one of the most important maritime regions in the world. Here, we focus not only on the immediate COVID-19 impacts on the extractive fisheries sector, but also on the capacity of the aquaculture and the canned industries to supply seafood markets before and during the pandemic. We synthesize multiple data sources from across the seafood supply chain to show the relative initial responses and variables of recovery during a pre-COVID-19 period (2015–2019) and during the pandemic (2020). Our study shows that seafood sectors and trade were disrupted by abrupt shifts in demand, supply and limitations on the movement of people and goods, with a wide range of impacts and consequences for the seafood sectors. We find that domestic landings, Galician aquaculture production and imports and exports of seafood products (fresh, live and frozen) in 2020 showed an important decrease. In contrast, the canned production and the imports and exports of prepared and preserved seafood products followed an increasing trend during the COVID-19 pandemic. We record a change in the consumption behavior of the Galician population, which significantly increased expenditure in fresh and canned seafood products during the first confinement. Overall, the Galician seafood sectors were able to ensure the supply of seafood products to the population during the period of confinement decreed as a result of the COVID-19 crisis. Proximity to markets, investment in domestic or nearby supply chains and the development of new technological innovations helped to avoid food shortages and loss of livelihoods in Galicia. Fishers and fishing enterprises have also acted collectively to reassert their rights to provide essential and high quality seafood products to the Galician population, their livelihoods and safe working conditions, and have leveraged relationships and collaborations with their government counterparts to continue fishing.